Self-awareness of one's own difficulties and the severity of depression in adolescents with autism spectrum disorders - Agnieszka Siedler; Edyta Idczak-Paceś (Studia z Teorii Wychowania)
Autism Spectrum Disorders (ASD) are marked by significant challenges in social interaction, communication, and by restricted, repetitive behaviors and interests. These disorders often coexist with emotional issues like depression. The present study investigates the hypothesis that discrepancies between self-assessments of symptoms by adolescents with ASD and their parents' assessments contribute significantly to the severity of depressive symptoms. This mismatch may cause adolescents to feel misunderstood and isolated, lacking necessary support. A sample of 223 adolescents and their parents or legal guardians participated, utilizing the Autism Spectrum Quotient (AQ) and the Autism Spectrum Rating Scale for ASD symptom assessment, along with the CDI-2 questionnaire to evaluate depressive symptoms from multiple perspectives. Correlational analyses between ASD symptoms and depressive symptoms reported by adolescents and their parents revealed significant positive correlations, underscoring a strong relationship between ASD-related difficulties, the severity of depressive symptoms, and self-awareness of these difficulties. Variance analysis highlighted differences in depressive symptom perception between adolescents and their parents, as well as across different ASD symptom intensity levels. Post-hoc analyses indicated significant differences in depressive symptom intensity assessed through self-reports among groups with varying ASRS scores. These findings emphasize the complex interplay between ASD and depression, particularly highlighting the impact of self-awareness and parental perception of adolescents' difficulties on depressive symptomatology. This underscores the importance of accurate and early diagnosis of ASD to mitigate the risk of depression, suggesting that both self-report and parental assessments are critical in understanding and addressing the mental health needs of adolescents with ASD.